2001
DOI: 10.1161/hc3501.095479
|View full text |Cite
|
Sign up to set email alerts
|

Previous Cytomegalovirus Infection and Restenosis After Coronary Stent Placement

Abstract: Background-Reactivated cytomegalovirus may promote neointima formation after percutaneous coronary interventions by facilitating cell cycle progression through inhibition of the eukariotic tumor suppressor protein p53. This prospective study sought to investigate the effect of previous cytomegalovirus infection on restenosis after coronary stenting. Methods and Results-In 551 consecutive patients with successful stent placement, we determined cytomegalovirus IgG titers. Primary and secondary end points were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…1a, 3a), previous suggestions of CMV-dependent pathomechanisms in neointimal hyperplasia due to inhibition of proapoptotic p53 [19]are not supported by our current findings. While these authors reported that prior CMV infection increased the risk of restenosis after directional atherectomy [19], others found no correlation between previous CMV infection and increased risk of restenosis after stenting [16]. As to Chlamydia pneumoniae, we report acute infection (MOMP) and chronic persistence (cHSP60, fig.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…1a, 3a), previous suggestions of CMV-dependent pathomechanisms in neointimal hyperplasia due to inhibition of proapoptotic p53 [19]are not supported by our current findings. While these authors reported that prior CMV infection increased the risk of restenosis after directional atherectomy [19], others found no correlation between previous CMV infection and increased risk of restenosis after stenting [16]. As to Chlamydia pneumoniae, we report acute infection (MOMP) and chronic persistence (cHSP60, fig.…”
Section: Discussionmentioning
confidence: 62%
“…As suggested, chronic immune-mediated inflammatory responses in atherosclerosis may be antigen-specific and directed against autoantigens or pathogen-derived structures [3]. Although possible associations between restenosis with specific infectious agents have been proposed by seroepidemiological studies that focused on cytomegalovirus (CMV), Chlamydia pneumoniae and intimal pathogen burden [15, 16, 17, 18, 19, 20], to our knowledge, its presence in ISR lesions has not yet been determined. Likewise, with regard to the regulation of neointimal cellularity in clinical restenosis, proliferative activity of smooth muscle cells remains controversial [21, 22], whereas low levels of intimal apoptosis post-balloon angioplasty compared to primary atheroma were previously reported by our group [23].…”
Section: Introductionmentioning
confidence: 99%
“…HCMV re-activation may be involved in the pathogenesis of solid organ allograft rejection, and graft atherosclerosis [9,10]. Existing HCMV infection appears to be a strong independent risk factor for restenosis after coronary atherectomy [11][12][13]. Although still far from consistent, population studies have generally demonstrated an association between HCMV seropositivity and the increased risk of coronary atherosclerosis [2,3,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Both a clear correlation [26,27] between HCMV seropositivity and restenosis and no correlation at all [28,29] have been reported. Serum IgG and IgM antibodies to HCMV in individuals proof merely the presence of HCMV but do not indicate the ability or intention of the virus to stimulate [10,11], postpone [13], or inhibit cell proliferation [8,9].…”
Section: Discussionmentioning
confidence: 97%